Papyri from the Washington University Collection St. Louis, Missouri - Maresch, Klaus. author. aut Link
XV, 247 p. 32 illus.
Keywords: Texts from the papyrus collection of Washington University have already appeared in Veme B. Schuman, Washington University Papyri 1: Non Literary Texts (American Studies in Papyrology 17), Chico (Califomia) 1980. This new volume is intended as a continuation, and the texts appearing in it have been numbered accordingly, subsequent to Schuman's. We divided our texts at an early stage, and while we have consulted each other extensively since then, we retain chief responsibility each for the pieces we began with: Maresch for 69-72, 77, 78, 80, 83, 86, 88, 90-94, 101, 102, 104, 107, and 108; Packman for 62-68, 73-76, 79, 81, 82, 84, 85, 87, 89, 95-100, 103, 105, and 106. The editors of P.Wash.Univ. II were brought together by Reinhold Merkelbach, to whom they are grateful for his continuing support and advice. Our thanks are due to the Deutsche Forschungsgemeinschaft, whose suppon enabled Maresch to visit St. Louis in 1988, and the American Council of Leamed Societies, whose fellowship brought Packman to Cologne in 1989- 90. An ACLS grant in 1966 made possible the photographs on which has depended most of the work done on the collection since: Some of them appear in the plates of this volume.